Development and validation of an immune-related gene pairs signature in colorectal cancer - Wu, Jianping; Zhao, Ying; Zhang, Juanwen; Wu, Qianxia; Wang, Weilin (Oncoimmunology, 2019)
Although the outcome of colorectal cancer (CRC) patients has improved significantly with the recent implementation of annual screening programs, reliable prognostic biomarkers are still needed due to the disease heterogeneity. Increasing pieces of evidence revealed an association between immune signature and CRC prognosis. Thus, we aim to build a robust immune-related gene pairs (IRGPs) signature that can estimate prognosis for CRC. Gene expression profiles and clinical information of CRC patients were collected from six public cohorts, divided into training cohort (n = 565) and five independent validation cohorts (n = 572, 290, 90 177 and 68, respectively). Within 1534 immune genes, a 19 IRGPs signature consisting of 36 unique genes was constructed which was significantly associated with the survival. In the validation cohorts, the IRGPs signature significantly stratified patients into high- vs low-risk groups in terms of prognosis across and within subpopulations with early stages disease and was prognostic in univariate and multivariate analyses. Several biological processes, including response to bacterium, were enriched among genes in the IRGPs signature. Macrophage M2 and mast cells were significantly higher in the high-risk risk group compared with the low-risk group. The IRGPs signature achieved a higher accuracy than commercialized multigene signatures for estimation of survival. When integrated with clinical factors such as sex and stage, the composite clinical and IRGPs signature showed improved prognostic accuracy relative to IRGPs signatures alone. In short, we developed a robust IRGPs signature for estimating prognosis in CRC, including early-stage disease, providing new insights into the identification of CRC patients with a high risk of mortality.